Digital Marketing Mix Strategy of Klinik Pratama Asera Cantika Sumbawa - Pradnyana, I Gde Yoghie; Rohendi, Aceng; Widjaja, Yani Restiani (Asosiasi Ahli Administrasi Indonesia, 2025)
The digital era has brought significant changes to marketing strategies, including in the healthcare sector. Klinik Pratama Asera Cantika Sumbawa faces increasingly intense competition, requiring effective marketing strategies to enhance competitiveness and attract more patients. This study aims to analyze the implementation, challenges, and solutions of digital marketing mix strategies to attract and retain customers at Klinik Pratama Asera Cantika Sumbawa. This research employs a qualitative approach using observation and focused interviews. The study's informants include the marketing team and social media team of Klinik Pratama Asera Cantika Sumbawa. The researcher focuses on the implementation of the P-based digital marketing mix strategy, as well as the factors that hinder and support its success in reaching the target market. The findings indicate that Klinik Pratama Asera Cantika Sumbawa has comprehensively implemented the digital marketing mix strategy using the P approach, covering product, price, place, promotion, process, people, and physical evidence. However, internal challenges such as budget constraints in marketing communication, difficulties in building customer loyalty due to intense competition, and accessibility and service convenience issues remain major obstacles in optimizing digital strategies. To address these challenges, the clinic has adopted various solutions, including online consultation systems, social media and influencer-based promotional strategies, and improvements in facilities and services to enhance customer experience. By implementing more focused and adaptive strategies, the clinic aims to strengthen its competitive advantage and maintain customer loyalty amid the increasingly competitive beauty industry.